Enhancement of enzymatic saccharification of corn stover with sequential Fenton pretreatment and dilute NaOH extraction. (October 2015) - He, Yu-Cai; Ding, Yun; Xue, Yu-Feng; Yang, Bin; Liu, Feng; Wang, Cheng; Zhu, Zheng-Zhong; Qing, Qing; Wu, Hao; Zhu, Cheng; Tao, Zhi-Cheng; Zhang, Dan-Ping
Graphical abstract: Highlights: Sequential Fenton pretreatment and dilute NaOH extraction was used for the pretreatment. The optimum pretreatment conditions were obtained. Corn stover (60 g/L) could be saccharified effectively. The recovered hydrolyzates could be fermented into ethanol efficiently. The combination pretreatment has high potential application. Abstract: In this study, an effective method by the sequential Fenton pretreatment and dilute NaOH extraction (FT-AE) was chosen for pretreating corn stover. Before dilute NaOH (0.75 wt%) extraction at 90 °C for 1 h, Fenton reagent (0.95 g/L of FeSO4 and 29.8 g/L of H2 O2 ) was employed to pretreat CS at a solid/liquid ratio of 1/20 (w/w) at 35 °C for 30 min. The changes in the cellulose structural characteristics (porosity, morphology, and crystallinity) of the pretreated solid residue were correlated with the enhancement of enzymatic saccharification. After being enzymatically hydrolyzed for 72 h, the reducing sugars and glucose from the hydrolysis of 60 g/L FT-AE-CS pretreated could be obtained at 40.96 and 23.61 g/L, respectively. Finally, the recovered hydrolyzates containing glucose had no inhibitory effects on the ethanol fermenting microorganism. In conclusion, the sequential Fenton pretreatment and dilute NaOH extraction has high potential application in future.